2011
DOI: 10.1186/1471-2350-12-9
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of germline BRCA1 and BRCA2sequence alterations in Slovenian population

Abstract: BackgroundThe BRCA1 and BRCA2 mutation spectrum and mutation detection rates according to different family histories were investigated in 521 subjects from 322 unrelated Slovenian cancer families with breast and/or ovarian cancer.MethodsThe BRCA1 and BRCA2 genes were screened using DGGE, PTT, HRM, MLPA and direct sequencing.ResultsEighteen different mutations were found in BRCA1 and 13 in BRCA2 gene. Mutations in one or other gene were found in 96 unrelated families. The mutation detection rates were the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 76 publications
6
28
0
Order By: Relevance
“…c.843_846delCTCA and c.1687C > T were both detected in Slovenia (Stegel et al, 2011), Italy (Santarosa et al, 1998), Austria (Wagner et al, 1998), Germany (Meindl and German Consortium for Hereditary Breast and Ovarian Cancer, 2002), Czech Republic (Machackova et al, 2008) and Slovakia (Konecny et al, 2011), while Switzerland reported only c.1687C > T (Schoumacher et al, 2001). BRCA1 c.5251C > T was found in Slovenia (Stegel et al, 2011), Austria (Wagner et al, 1998), Germany (Meindl and German Consortium for Hereditary Breast and Ovarian Cancer, 2002), Poland (Gorski et al, 2004) and Greece (Konstantopoulou et al, 2008). BRCA1 c.676delT was detected in Poland (Gorski et al, 2004) and Germany (Dong et al, 1998) and BRCA2 c.9371A> T was detected in Poland (Kozlowski and Krzyzosiak, 2001) and in Slovenia as an UV (Stegel et al, 2011).…”
Section: Exonmentioning
confidence: 95%
See 3 more Smart Citations
“…c.843_846delCTCA and c.1687C > T were both detected in Slovenia (Stegel et al, 2011), Italy (Santarosa et al, 1998), Austria (Wagner et al, 1998), Germany (Meindl and German Consortium for Hereditary Breast and Ovarian Cancer, 2002), Czech Republic (Machackova et al, 2008) and Slovakia (Konecny et al, 2011), while Switzerland reported only c.1687C > T (Schoumacher et al, 2001). BRCA1 c.5251C > T was found in Slovenia (Stegel et al, 2011), Austria (Wagner et al, 1998), Germany (Meindl and German Consortium for Hereditary Breast and Ovarian Cancer, 2002), Poland (Gorski et al, 2004) and Greece (Konstantopoulou et al, 2008). BRCA1 c.676delT was detected in Poland (Gorski et al, 2004) and Germany (Dong et al, 1998) and BRCA2 c.9371A> T was detected in Poland (Kozlowski and Krzyzosiak, 2001) and in Slovenia as an UV (Stegel et al, 2011).…”
Section: Exonmentioning
confidence: 95%
“…Accordingly, they were detected in most of the Slavic countries (Slovenia (Stegel et al, 2011), Serbia (Brankovic-Magic, 2006, Czech Republic (Machackova et al, 2008), Slovakia (Konecny et al, 2011) and Poland (Gorski et al, 2004)). Screening in Ukraine and Bulgaria is still incomplete but there is record of Canadians of Table 5 BRCA2 sequence variants detected in Croatian candidates.…”
Section: Comparison Of Detected Mutations With Surrounding European Cmentioning
confidence: 97%
See 2 more Smart Citations
“…This was also previously described as a polymorphism, rs28897710, in Slovenian population. 32 The second VUS was c.5986G>A (p.Ala1996Thr) in exon 11, which has been previously described as a harmful variant in a Croatian BC study 33 and is reported in ClinVar five times in HBOCS patients, with conflicting interpretation of pathogenicity. The third one was c.7445C>T (p.Thr2482Ile) in exon 15.…”
Section: Discussionmentioning
confidence: 99%